Development of kiwi fruit leather incorporated with hydrocolloids and betacyanin microcapsules: Rheological behaviour and release kinetics of betacyanin - G.V.S. Bhagya Raj; Kshirod Kumar Dash; Rafeeya Shams; Shaikh Ayaz Mukarram; Bela Kovács (Applied Food Research)
The kiwi fruit leather incorporated with betacyanin microcapsules was prepared using three hydrocolloids namely xanthan gum, gellan gum, and guar gum. The four-kiwi fruit puree prepared for the study were kiwi fruit puree without hydrocolloid (CP), with xanthan gum (XE), with gellan gum (EP), and with guar gum (UP). The influence of various hydrocolloids and temperatures on rheological properties of kiwi fruit puree was investigated using the Cross, Carreau, and modified Powell model. The apparent viscosity was decreased with increase in shear rate and rise of temperature. The incorporation of hydrocolloid also increased viscosity of prepared puree. Cross model (R2>0.989) found to fit the apparent viscosity with respect to shear rate. The flow behaviour index of four kiwi fruit puree samples was found to be less than one depicting pseudoplastic fluid with shear thinning behaviour. For dynamic rheology study in the frequency range of 1–60 rad/s, the storage modulus was higher than loss modulus at specific frequency that implies, elastic properties of puree were dominant over the viscous ones suggesting the weak gel-like network of kiwi fruit puree. The glass transition temperature of prepared kiwi fruit leathers ranged from 59 to 64 °C. The in vitro betacyanin release from the leather sample was studied and Peppas-Sahlin model was observed to be one of the ideal model when compared with the other kinetic models. The development of kiwi fruit leather with hydrocolloids and betacyanin microcapsules represented a successful strategy to create a functional snack that combines health benefits with consumer-desirable sensory attributes.